Pengembangan Aplikasi Simasjid Menggunakan Metode Extreme Programming - Bagas Ardianto; Jaroji Jaroji; M.Asep Subandri (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
The annual qurban ritual is performed by Nurul Huda Mosque, although a recurring activity, it often encounters challenges in its execution. Issues such as manual participant registration using books and records, non-transparent meat distribution, and the use of traditional paper-based coupon systems for persistent meat allocation. To address these challenges, this study aims to develop a web-based Simasjid application with qurban management features and examine its impact on congregants and qurban participants.The research focuses on the implementation of the Extreme Programming method for developing the Simasjid application. Extreme Programming, as an Agile approach, provides a flexible and adaptive software development model. This method accommodates evolving user requirements and includes stages such as planning, design, coding, and testing.